PERTUKARAN MATA-MATA RUSIA TERHADAP AMERIKA SERIKAT DI KOTA WINA, AUSTRIA, TAHUN 2010 - Vidya Mahayani, Dewa Ayu Putu; Dharmiasih, D.A. Wiwik; Suwecawangsa, Adi P. (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2019)
ABSTRACT The issue of spying has an important role in the dynamics of two countries. There were incident of the arrested Russian spies in United States. The arrested Russian spies incident happenedwhenRussia and the United States build the cooperation in economic and military. Russia's decision to accept the United States offer helps improve the country's image. Russia also wants to save the economic and military cooperation that just begin with the United States. This study analyzes the influence of Russia's image in foreign policy. This research has a span of time between 2005-2010. Research data is collected from various sources of network sites and scientific research relating to this research. The concepts usedin this researchareespionage, image, and foreign policy.This study focuses on Russia's decision to accept United States offers of spy swap to build an image and continue the cooperation that has been established. Keywords: Spy Swap, Image, Foreign Policy